2020
DOI: 10.1111/dom.13962
|View full text |Cite
|
Sign up to set email alerts
|

Enrolment criteria for diabetes cardiovascular outcome trials do not inform on generalizability to clinical practice: The case of glucagon‐like peptide‐1 receptor agonists

Abstract: Aim: To evaluate the generalizability of cardiovascular outcome trials (CVOTs) on glucagon-like peptide-1 receptor agonists (GLP-1RAs), we assessed what proportion of real-world patients with type 2 diabetes (T2D) constitute true CVOT-like populations. Materials and Methods: We applied inclusion/exclusion (I/E) criteria of each GLP-1RA CVOT to a cross-sectional database of 281 380 T2D patients from Italian diabetes outpatient clinics. We calculated the proportion of patients eligible for each CVOT and compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 30 publications
1
32
0
Order By: Relevance
“…A regular comprehensive assessment of the patient's health status and care needs, based on a validated and uniform approach like the interRAI tool [42] may allow for key decision making in the care of older persons [43,44]. Our results suggest that it is also fundamental that caregivers develop the competence to recognize the spiritual and/or existential dimension in patients in their daily work environment.…”
Section: Discussionmentioning
confidence: 96%
“…A regular comprehensive assessment of the patient's health status and care needs, based on a validated and uniform approach like the interRAI tool [42] may allow for key decision making in the care of older persons [43,44]. Our results suggest that it is also fundamental that caregivers develop the competence to recognize the spiritual and/or existential dimension in patients in their daily work environment.…”
Section: Discussionmentioning
confidence: 96%
“…In a recent multicenter study conducted on over 280,000 subjects with T2D treated in outpatients diabetes clinic in Italy, our group showed that, at most, one-third of these "real-world" patients would be included in each specific cardiovascular outcome trial (CVOT) on GLP-1RAs according to inclusion/exclusion (I/E) criteria ( Figure 2). 16 Moreover, more than 50% of subjects attending these clinics, representative of all diabetes subjects in Italy, would not be included in any of these trials. Similar results have also been reported from analyses of patients with T2D treated in the Unites States.…”
Section: From Experimental Randomized Controlled Trial To Real-world mentioning
confidence: 99%
“…17 In addition, after applying sophisticated approaches of data analyses to select a group of subjects with CVOT-like clinical characteristics (ie, with average clinical characteristics similar to CVOT), we found that the proportion of subjects selected from real-world clinical practice would be at most 8%. 16…”
Section: From Experimental Randomized Controlled Trial To Real-world mentioning
confidence: 99%
“…A regular comprehensive assessment of the patient's health status and care needs, based on a validated and uniform approach like the interRAI tool[43] may allow for key decision making in the care of older persons [44,45]. Our results suggest that it is also fundamental that caregivers develop the competence to recognize the spiritual and/or existential dimension in patients in their daily work environment.…”
Section: Quality Of Lifementioning
confidence: 96%